Teamwork competency scale (TCS) from the individual perspective in university students - Melany Hebles; Concepción Yániz-Ál; Manuel Alonso- (OmniaScience, 2022)
The main purpose of this study was to design and validate a scale to evaluate the development of teamwork competence of undergraduate students (TCS, teamwork competence scale). The research instrument used for validation and design has nine specific dimensions: Collective efficacy, learning orientation, establishing group goals, planning and coordination, communication, conflict management, problem solving, performance monitoring and back-up behavior. The sample consisted of a total of 802 freshmen of a Chilean university. For the statistical analysis, the method of partial least squares (PLS) was approached within a structural equation modeling (SEM). Results show that the TCS is a valid and reliable research instrument to assess the level of development of teamwork competence in undergraduate students.